Die Kinder vom Friedrichshof . The Children of the Commune - Großheim, Juliane (Unafilm Cologne, 2009)
Verzio FF Submission The commune of Otto Mühl, the acclaimed Vienna Actionist, was one of the most controversial artistic and social experiments of the 1970s. In the countryside, in the grounds of the Friedrichshof, unrestrained sexuality, common property, body art, and the consistent removal of any permanent relationships served as the foundation for this project. The most ambitious aim of this Austrian commune was Mühl 's third generation project — child production — which aimed to create a completely new human being. Twenty years later, in the summer of 1991, Mühl was arrested for child abuse and the community dissolved. The company's experiment was a dramatic failure. Through the eyes of these children, the film looks back at the community and examines what has become of the children of Mühl's utopia.